GRANITIC MAGMATISM IN THE NORTH QAIDAM EARLY PALEOZOIC ULTRAHIGH-PRESSURE METAMORPHIC BELT, NORTHWEST CHINA - Wu C.; Yang J.; Zheng L.; Shi R.; Chen S.; Wooden J.L.; Robinson P.T. (My University, 2006)
Three suites of granitic rocks are present in the early Paleozoic North Qaidam ultrahigh-pressure (UHP) metamorphic belt, which has eclogite ages of 466-495 Ma. The first suite consists of quartz monzodiorite + granodiorite + monzogranite, the second of monzogranite + two-mica granite + muscovite granite + syenogranite, and the third of granodiorite + monzogranite + biotite granite. The country rocks into which these bodies were intruded consist chiefly of medium- and high-grade Proterozoic gneisses and schists and Paleozoic sedimentary and volcanic rocks. Monzogranite of the first suite has a zircon SHRIMP age of 473 Ma, whereas syenogranite in the second suite has an age of 446 Ma, and granodiorite in the third suite has an age of 397 Ma. Rocks of the first and third suites have similar mineralogies consisting of plagioclase, hornblende, quartz, alkali feldspar, and biotite, whereas those of the second suite consist of potassium feldspar, quartz, muscovite, biotite, and plagioclase. Rocks of the first and third suites have I-type compositions with SiO2 = 61-69 wt%, Na2O/K2O >1, ANK <1, and Eu/Eu* = 0.7-1.0, whereas the second suite consists of S-type granites, with SiO2 = 70-76 wt%, Na2O/K2O <1, ANK >1, and Eu/Eu* = 0.1-0.3. The first suite is interpreted as island arc or active continental margin magmatism, the second as igneous activity related to collision between the Qaidam and Qilian blocks, and the third as post-collisional plutonic activity. Copyright © 2006 by V. H. Winston & Son, Inc. All rights reserved.
Keywords: Proterozoic; Precambrian::Proterozoic; Докембрий::Протерозой